Search with Learning from Prices: Does Increased Inflationary Uncertainty Lead to Higher Markups - Benabou, Roland; Gertner, Robert (Review of Economic Studies, 1993)
Aggregate cost uncertainty, arising from real shocks or unanticipated inflation, reduces the informativeness of prices by scrambling relative and aggregate variations. But when agents can acquire additional information, such increased noise may in fact lead them to become better informed, and price competition will intensify. We examine these issues in a model of search with learning, where consumers search optimally from an unknown price distribution while firms price optimally given consumers' search rules. We show that the decisive factor in whether inflation variability increases or reduces the incentive to search, and thereby market efficiency, is the size of informational costs.